Multi-Actors Collaboration in Ecolabelling Community Teak Forest Management in Southeast Sulawesi Province, Indonesia - M. Saleh S. Ali; Anas Nikoyan; Darmawan Salman; Eymal B. Demmalino; Idris Summase (International Journal of Agriculture System, 2015)
Forest management practice in Indonesia has changed from “the forest first” paradigm to “the forest second” paradigm which emphasis on balancing between ecological dynamics and social dynamics (economy, culture, and politics) in forest management. “The forest second” paradigm have been practiced in HJRE (Hutan Jati Rakyat Ecolabel or Ecolabling Community Teak Forest) program in Konawe Selatan District of Southeast Sulawesi Province, Indonesia. This paper was intended to explain the collaboration of the actors involve in the program at community level. Data used in this paper gathered from in-depth interview of various actors who have involved in this program at community level especially local people who have registered as members of KHJL (Koperasi Hutan Jati Lestari or Sustainable Teak Forest Cooperative) and actively involved in the program. These people selected as informants from 8 villages where this study conducted. Beside that, it was interviewed also other actors involved in the program. This study revealed that the actors involved in collaboration process of HJRE program at community level were householdmembers of KHJL, Management Unit, JAUH (Jaringan Untuk Hutan or Network for Forest), TFT (Tropical Forest Trust), Wood Industry (PT. KJL), Head of Villages, and Head of KRPH (Kesatuan Resort Pemangku Hutan or Forest Functionary Unit). All actors involved in collaboration process contributed R-O-N (Resources-Organization-Norms) capacities in the stage of development of HJRE program. Some actors contributed much or less on R-O-N or its combinations. The capacities contributed of the actors gradually from social initiation/ awareness stage up to expansion and sustainability stage were R/N – O/N – R – R – N/R.Degree of collaboration of the actors involved in the HJRE program were not the same. Some actors have high collaboration and some low collaboration. These situation determined by the power and interest of the actors.